Interspecific crossing between blue‐tailed damselflies Ischnura elegans and I. senegalensis in the laboratory. Issue 2 (15th March 2020) - Okude, Genta; Fukatsu, Takema; Futahashi, Ryo
Abstract: Ischnura species (Odonata) are among the most common damselflies in the world, which often exhibit female color polymorphisms. One morph, called androchrome, is similar to males in its color pattern, whereas the other morphs, generally referred to as gynochromes, exhibit female‐specific colors. In several Ischnura species, the female polymorphism is heritable, although molecular and genetic mechanisms remain largely unknown. The dominant‐recessive patterns of the female color morphs may differ between species. For example, androchromic females are dominant to gynochromic females in Ischnura elegans, whereas androchromic females are recessive in Ischnura senegalensis . Here we report a case of interspecific hybridization between a gynochrome female of I. elegans and a male of I. senegalensis in the laboratory. We obtained 61 hybrid adult offspring, of which all 31 females were of gynochrome morph. DNA analyses of the hybrids confirmed that nuclear DNA sequences were derived from both parent species, whereas mitochondrial DNA sequences were maternally inherited. In the hybrids, the postocular spots of female heads, the shape of male appendages, and the color of female's cerci resembled those of I. elegans, whereas the size of abdominal blue spots was similar to that of I. senegalensis . The shape of prothorax and basal abdominal markings were intermediate in females. The larval developmental traits and the morphological changes in the final larval instar of the hybrids were similar to those of I. senegalensis . To our knowledge, this is the first report of hybrids between two damselfly species with different dominant‐recessive patterns of female color morphs. Abstract : We report a successful case of interspecific crossing between blue‐tailed damselflies Ischnura elegans and I. senegalensis in the laboratory. We obtained 61 hybrid adult offspring with phenotypes intermediate between the two parent species, of which all 31 females were of gynochrome morph. We also describe larval developmental traits and morphological changes in the final larval instar of the hybrids in detail.